Music History Pedagogy on the Ground Floor - Davis, James A. (Musica Docta, 2016)
This article urges musicologists to consider ways in which to connect with pre-collegiate education. Ideas presented include connecting with local schools and national teacher organizations, creating courses and workshops, and looking for ways our research might be presented to a broader audience. Extending our outreach promotes the health of our discipline and strengthens our presence in the face of financial setbacks and imposed curricular revisions.